CONSUMER INTENTION OF PURCHASING ORIGINAL AND COUNTERFEIT PRODUCTS; A CASE STUDY OF LOUIS VUITTON WALLET - Kevin Kristanto Hadiwijaya (iBuss Management, 2015)
Counterfeit products have spreads worldwide, and Indonesia is no exception. Losses due to rampant counterfeiting accounted to 34.2 trillion rupiah in GDP.  This research is conducted with the aim to find out the most influencing factor in improving customer intention to buy original product and at the same time decreasing the number of counterfeit product on the market, especially in Surabaya. The data was gathered using simple random sampling by distributing questionnaires to 130 respondents in Surabaya. The data was analyzed by using Multiple Linear Regression Analysis. The result shows that attitude, price quality inference, past purchase, personal appearance, and social influence has significant impact on consumer intention to purchase original and counterfeit product. Meanwhile, price quality inference is the most influencing factor affecting consumer’s intention to purchase both original and counterfeit Louis Vuitton walletKeywords: Counterfeit products, Intention to purchase, Price quality inference